The relationship of religion, religiosity, and parental communication in the sexual behaviors of Filipinos aged 18-25 years in the United States and the Philippines - Ivy C. Tuason; Racidon Bernarte; Fanglong Dong (JMIR Publications, 2017)
This cross-sectional survey research aims to explore and compare the relationship of religion, religiosity, and parental communication to the sexual behaviors of Filipinos aged 18-25 years in the United States and the Philippines. The Duke University Religion Index and Parent-Teen Sexual Risk Communication Scale-III was used to measure religiosity and parental communication. There were 130 participants living in the United States and 247 living in the Philippines included in this study. Among respondents from the Philippines, low levels of parental communication were associated with an increased report for the lack of condom use during the last intercourse. Catholics had a decreased likelihood of alcohol or illicit drug use before intercourse, having had multiple sex partners, and engaging in casual sex. Those who had low levels of religiosity were associated with reports of having had casual sex. Among the United States respondents, those who engaged in alcohol or illicit drug use before sexual intercourse were associated with decreased organizational religious activities. The findings of this study confirmed the need for comprehensive and culturally appropriate approaches to health promotion programs that incorporate religious and familial factors appropriate for Filipinos.